Peningkatan Aktivitas dan Hasil Belajar Peserta Didik pada Sistem Organisasi Kehidupan Melalui Model Guided Discovery Learning Kelas VII J SMPN 2 Demak - Sri Dwi Sulistyowati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
In the effort of improving the learning process, teachers must try to apply learning models that are appropriate to the character of the subjects so that the students are more active and learning becomes more meaningful. Based on data taken from the results of the daily tests of class VII J, as many as 67.65% of the students scored below the passing grade, and the average daily tests were 67.73. Factors causing the low learning outcomes are learning models that are still teacher-centered, so students are less active. Therefore we need an effort to improve the students’ activities and learning outcomes. This study aims to improve the students’ activities and learning outcomes in the Organizational System of Life through Guided Discovery Learning Model. The subjects of this study were the students of class VII J of SMPN 2 Demak, totaling 34 people, consisting of 10 men and 24 women. This research is a Classroom Action Research conducted in two cycles. The research is said to be successful if the average daily test minimum reaches passing grade (80), classical completeness is at least 80%, and the percentage of student activity is at least 75%. The data collection techniques are using student test results, observation sheets of teacher and student activities. The results showed an average grade of 82.0 in the first cycle and 90.9 in the second cycle. Completeness of classical learning outcomes reached 82.34% in the first cycle and 94.12% in the second cycle.